Contrasting adaptation responses by squatters and low-income tenants in Khulna, Bangladesh. (April 2013) - Roy, Manoj; Hulme, David; Jahan, Ferdous
This paper examines patterns of adaptive behaviour in low-income settlements (1) in Khulna, Bangladesh's third largest city. It contrasts the adaptive behaviours of "squatter" households who "own" their land with those of tenants who rent dwellings from private landlords, and finds significant differences between the adaptive behaviours of owners and renters. This is important, as most knowledge about low-income settlements in Bangladesh originates from "owned" settlements – often called "public settlements", as the land is officially public land. But the future growth of low-income settlements in the country is likely to be increasingly on private land, with rented dwellings. Policy lessons generated from settlements with "squatters" may be inappropriate for the next generation of "slums" that will house millions of rural migrants and people displaced by climate change. The conclusions argue that agencies seeking to assist low-income households in Bangladesh will need to craft different strategies for settlements according to different types of land tenure.